Supplementary Material S1, S2 from Global cultural evolutionary model of humpback whale song - Lies Zandberg (11180220); Robert F. Lachlan (3377966); Luca Lamoni (5236373); Ellen C. Garland (9633176) (2021)
Population sizes and Validation of ABC model